STRATEGI PEMERINTAH DAERAH KABUPATEN BANDUNG BARAT DALAM PENGELOLAAN WISATA ALAM - Kandias, Muhammad Rizki Nur; Sukaesih, Poni (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study aims to examine the strategies of the Tourism and Culture Office of West Bandung Regency in managing natural tourism. A descriptive qualitative approach was employed, with data collected through literature review, field observation, and in-depth interviews with purposively selected informants. The findings indicate that the management strategies have been effectively implemented in terms of planning, coordination, and learning processes. However, challenges remain in policy implementation and the development of supporting infrastructure. An adaptive approach involving regular evaluations and recognition efforts has been undertaken, yet improvements are still needed in inter-party communication and program implementation effectiveness. The study recommends policy renewal, enhanced community participation, cross-sector collaboration, utilization of digital technology, and internal capacity strengthening. This research serves as a valuable reference for formulating strategic policies in sustainable natural tourism management based on local potential.